2011
DOI: 10.1161/circulationaha.110.012112
|View full text |Cite
|
Sign up to set email alerts
|

Rottlerin Increases Cardiac Contractile Performance and Coronary Perfusion Through BK Ca++ Channel Activation After Cold Cardioplegic Arrest in Isolated Hearts

Abstract: Background Cardioplegia and cardiopulmonary bypass(CP/CPB) subjects myocardium to complex injurious stimuli that can result in cardiomyocyte and vascular contractile abnormalities. Rottlerin, originally identified as a PKCδ inhibitor has a number of known additional effects that may be beneficial in the setting of CP/CPB. We tested the hypothesis that rottlerin would mitigate deleterious effects associated with CP/CPB. Methods and Results Langendorff-perfused isolated rat hearts were subjected to 2 hours int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…BKCa activation with rottlerin significantly improved LVDP and dP/dt, as well as promoted enhanced coronary flow. 36 We have also confirmed specificity of rottlerin's effects using wildtype and BKCa KO mice, as well as verified significant cardioprotection with rottlerin-supplemented cardioplegia in a pig model of cardioplegia and cardiopulmonary bypass 37 (unpublished observations). Myocardial stunning associated with mild ischemic insults is an additional sion pattern SK1>SK2>SK3.…”
Section: Structure/functionsupporting
confidence: 64%
See 1 more Smart Citation
“…BKCa activation with rottlerin significantly improved LVDP and dP/dt, as well as promoted enhanced coronary flow. 36 We have also confirmed specificity of rottlerin's effects using wildtype and BKCa KO mice, as well as verified significant cardioprotection with rottlerin-supplemented cardioplegia in a pig model of cardioplegia and cardiopulmonary bypass 37 (unpublished observations). Myocardial stunning associated with mild ischemic insults is an additional sion pattern SK1>SK2>SK3.…”
Section: Structure/functionsupporting
confidence: 64%
“…55 Indeed, BKCa activation during hypothermic IR significantly increases coronary flow, which is associated with improved function. 36 In addition, precipitating conditions of ischemic heart disease (hypercholesterolemia, diabetes, and metabolic syndrome) are all associated with impaired vasodilation and altered vasoreactivity. A large body of work (outside the scope of the current review) demonstrates that vascular perturbations in these diseases are all associated with altered expression, activity, and upstream signaling associated with BKCa channel subunits (for review 2,56 ).…”
Section: Skca and Ventricular Arrhythmia/hfmentioning
confidence: 99%
“…We recently demonstrated that the small molecule rottlerin (mallotoxin) enhances cardioprotection following ischemic cardioplegic arrest and reperfusion (CP/R) in a rat model of mild ischemic injury and myocardial stunning (10). Early evidence indicated that the cardioprotective effect of rottlerin was mediated by BKCa channels as demonstrated by pharmacological inhibition of the channel with paxilline.…”
Section: Mitochondrial Kmentioning
confidence: 99%
“…Isolated heart model of CP/R was performed similar to previous publications (10,11). FVB WT and kcnma1…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation